PENGARUH DISIPLIN KERJA, BUDAYA KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT MATAKALI KABUPATEN POLEWALI MANDAR - Abdul Jalil; Muhammad Idris; Muhammad Salim (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
This study aims to analyze the effect of work discipline, work culture and competence partially and simultaneously on employee performance at the Matakali District Office, Polewali Mandar Regency. The population in this study were all employees who worked at the Matakali Subdistrict Office of Polewali Mandar Regency, amounting to 37 people. Because the population is less than 100 people, the sample is determined by using a saturated sampling technique (census). So that the sample used in this study were 37 people. The data collection technique was carried out through a questionnaire/questionnaire where each respondent's answer was assessed using a score according to the Likert scale. The results of this study indicate that the results of the F test or simultaneous testing show that the Fcount value is 12.398 and Ftable is 2.89. So it shows that Fcount > Ftable with a significance of 0.000 < 0.05. These results indicate that work discipline, work culture and competence simultaneously have a significant effect on employee performance at the Matakali District Office, Polewali Mandar Regency. From the description of the t test, it is known that work discipline, work culture and competence partially each have a positive and significant effect on employee performance at the Matakali District Office, Polewali Mandar Regency. Furthermore, the work discipline variable is the most dominant influencing variable with a beta value of 0.519. Keywords: Work Discipline, Work Culture, Competence and Performance